Застосування мереж Петрі для аналізу КВ-граматик - Spectorsky, I. Ya. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2011)
The scheme of the use of Petri nets for the study of some properties of the CF-grammars is proposed. This method, enables, in particular, to investigate the emptiness and finiteness of language, generated by given CF-grammar, using tree cover of the relevant Petri net. Additionally, the proposed method allows to formulate the necessary conditions for the generation of a given word by CF-grammar in terms of a matrix analysis of the relevant network.